AB0137 Jak Inhibition by Tofacitinib Improves Rheumatoid Cachexia in a Rabbit Experimental Model That Reproduces the Lipid Paradox in Humans. (9th June 2015) - Perez-Baos, S.; Barrasa, J.I.; Gratal, P.; Little, R.D.; del Barrio, F.; Herrero-Beaumont, G.; Largo, R.
Abstract : Background: Rheumatoid cachexia (RC) is a complication of rheumatoid arthritis (RA), affecting up to 30% of patients, particularly those with a high degree of systemic inflammation. It is characterized by loss of body cell mass, together with fat mass gain, and may be linked to an increased risk of cardiovascular (CV) disease. However, the lipid profile of RA patients often appears normal or even lower than that found in a healthy population. In RA patients, higher levels of inflammatory markers are inversely correlated with total cholesterol levels, a phenomenon known as "the lipid paradox". Anti-inflammatory therapies appear to increase circulating lipids, yet this occurs without a corresponding increase in CV risk. Tofacitinib (TOFA) is an anti-inflammatory, Janus Kinase (JAK) inhibitor that ameliorates joint destruction in RA, with an unknown role in RC. Objectives: We aimed to analyze the effect of TOFA on RC and the "lipid paradox" observed during this complication. Methods: We induced an inflammatory state similar to human RC in 20 rabbits, that were fed with a high fat diet (4%cholesterol+2%peanut oil) (1). Rabbits underwent intra-dermal immunization with OVA followed by weekly, bilateral intra-articular OVA injections over 4 weeks (RC group). Two weeks after the first intra-articular injection, 10 animals started TOFA treatment (10mg/kg/day, orally) until the end of the study (RC+TOFA group). 10 healthy rabbits treated with the high fat diet were used as controls. All animals were sacrificed 6 weeks after challenge, when synovial and serum samples were collected. Results: RC animals demonstrated significantly reduced weight gain compared to controls that was partially reverted by TOFA treatment (table ). RC animals also showed a decrease in serum lipid levels compared to controls. TOFA induced an increase in total cholesterol and the total cholesterol/HDL ratio compared to RC animals. C-reactive protein (CRP) levels were dramatically increased in RC animals compared to controls, while a significant reduction was observed in the RC + TOFA group compared to RC group (p=0.006). Synovial histopathology, measured by Krenn score, showed lower synovial inflammation in the RC+TOFA group compared to RC animals. Subchondral bone mineral density (BMD) was lower in the RC group compared to controls (p<0.05). TOFA treatment also partially prevented the loss of subchondral BMD in RC animals [subchondral BMD (gr/cm 2 ): RC: 0.48±0.02; RC+TOFA: 0.55±0.01; p=0.004]. Conclusions: Our experimental model of RC reflects lipid metabolism observed in human RC and could be used for future mechanistic and therapeutic studies. In this regard, TOFA ameliorated systemic and articular inflammation, as well as clinical manifestations associated with RC, namely, increased cholesterol and the total cholesterol/HDL ratio. Therefore, this TOFA-treated model mimics the "lipid paradox", showing that anti-inflammatory therapy is associated with an increase in the ratio total cholesterol/HDL cholesterol that, as we have demonstrated previously, is not associated with accelerated cardiovascular atherosclerosis (1). References: Romero FI et al. Pharmacological modulation by celecoxib of cachexia associated with experimental arthritis and atherosclerosis in rabbits. Brit J Pharmacol, 2010 Disclosure of Interest: None declared